Enzyme inhibitory activities of marine sponges against cholinesterase and 5?-reductase - Suciati,; Karma Rabgay,; Yunda Fachrunniza,; Tongchai Saesong,; Hadi, Tri Aryono; Tutik Sri Wahyuni,; Aty Widyawaruyanti,; Kornkanok Ingkaninan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Marine sponges have been the source of various metabolites with potent biological activities. In this study fifteen methanolic extracts of marine sponges, collected off the coast of Tabuhan Island, Banyuwangi, East Java, Indonesia were evaluated in relation to their cholinesterase and 5α-reductase inhibitory activities. The results revealed that the extract of Petrosia sp. inhibited the 5α-reductase enzyme at 100 µg/mL, with 61.21% inhibition, which is slightly lower than the positive control, finasteride, of 76.70%. The results of the cholinesterase inhibitory screening showed that three marine sponges namely, Callyspongia sp., Niphates olemda, and Agelas nakamurai presented notable cholinesterase inhibitory activities. The highest potency was found in A. nakamurai, with an IC50 value of 1.05 µg/mL. All three samples inhibited both acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE), however, the extract of N. olemda showed a higher inhibition against AChE compared to BuChE. The chemistry of the Callyspongia sp., N. olemda and A. nakamurai were investigated using thin layer chromatography and 1H NMR methods. The results suggested the presence of terpenes and alkaloids in the samples. Further study is needed to determine the metabolite responsible for cholinesterase inhibitory activity.